MODERN FACTORS OF FORMATION OF ECONOMIC CULTURE OF FUTURE TRANSPORT TECHNOLOGY TECHNICIANS (Innovative professional education, 2025)
The article examines the contemporary factors influencing the formation of economic culture among future transport technology technicians in the context of dynamic socio-economic changes and the digitalization of the economy. The necessity of integrating economic knowledge into professional training to enhance graduates’ competitiveness in the labor market is substantiated. Particular attention is paid to the impact of pedagogical innovations, an interdisciplinary approach, and digital technologies on the development of economic culture
Keywords: professional mobility, strategic planning, digital economy, educational innovations, socio-economic adaptation